Sinorhizobium meliloti Plasmid pRm1132f Replicates by a Rolling-Circle Mechanism - Barran, L. R. (American Society for Microbiology, 2001)
pRm1132f isolated from Sinorhizobium meliloti is a group III rolling-circle-replicating (RCR) plasmid. At least seven of eight open reading frames in the nucleotide sequence represented coding regions. The minimal replicon contained a rep gene and single- and double-stranded origins of replication. Detection of single-stranded plasmid DNA confirmed that pRm1132f replicated via an RCR mechanism.